Titanium Complex Containing a Saligenin Ligand - New Universal Post-Metallocene Polymerization Catalyst: Copolymerization of Ethylene with Higher α-Olefins - Rishina, Laura A.; Lalayan, Svetlana S.; Gagieva, Svetlana Ch.; Тuskaev, Vladislav А.; Shchegolikhin, Alexander N.; Shashkin, Dimitri P.; Kissin, Yury V. (Journal of Research Updates in Polymer Science, 2015)
Copolymerization reactions of ethylene with three α-olefins, 1-hexene, 1-octene and 1-decene, were carried out with a new post-metallocene catalyst based on Ti complex with a bidentate saligenin-type ligand I and two co catalysts, MAO and a combination of AlEt2Cl and MgBu2. Ability of the I - AlEt2Cl - MgBu2 system to copolymerize α-olefins with ethylene is far superior to that of the I - MAO system. Reactivity of α-olefins in copolymerization reactions with ethylene decreases in the sequence: 1-hexene>1-octene>1-decene. Both catalyst systems, I - MAO and I - AlEt2Cl - MgBu2, contain several populations of active centers that greatly differs both in the average molecular weights and in composition of the copolymer molecules they produce. Active centers in both catalytic systems show significant tendency to alternate monomer units in copolymer chains.